THE FUNCTION OF FACILITIES AND INFRASTRUCTURE IN LEARNING GUIDANCE AND COUNSELING IN SCHOOLS - Lika; Neviyarni; Firman (Yayasan Citra Dharma Cindekia, 2022)
A success of guidance and counseling services is inseparable from the existence of facilities and infrastructure that support the provision of guidance and counseling services. Regulation of the Minister of National Education of the Republic of Indonesia No. 24 of 2007 concerning Standards for Facilities and Infrastructure for Schools firmly states that in education units it is mandatory to have the necessary facilities to facilitate the learning process. Therefore, schools strive to prepare facilities and infrastructure that are in accordance with standards, thereby facilitating the realization of optimal educational goals (Kemendiknas, 2007). The success of providing guidance and counseling services in schools is certainly greatly influenced by the utilization of the function of all guidance and counseling facilities and infrastructure in schools effectively and efficiently.